A Computer-Based Graphic Organizer With Embedded Self-Regulated Learning Strategies to Support Student Writing. (September 2019) - Hughes, Melissa D.; Regan, Kelley S.; Evmenova, Anya
Written expression is often difficult for students with and without learning disabilities. Research-based strategies to support this essential skill include self-regulated learning strategies, technology, and tools for planning and writing. This article describes a multifaceted technology-based writing intervention with embedded self-regulated learning strategies known as a computer-based graphic organizer or CBGO. The CBGO is described to assist teachers in their efforts to support upper elementary and middle school students to plan and write a high-quality persuasive paragraph. Recommendations for instructional use are discussed.